HUBUNGAN PERILAKU ANAK REMAJA MENGENAI PERMAINAN GAME ONLINE DENGAN KELUHAN KELELAHAN MATA DI KELURAHAN PADANG BULAN MEDAN TAHUN 2013 - Azmi Ervita Purnama; Alam Bakti Keloko; Taufik Ashar (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Complaining of eyestrain is one of the health problems in Indonesia, particularly eyes health that the prevalence is still quite high on students. In some areas, it is still a lack of attention on eyes health problems especially on children in Indonesia. This is proven by the presence of school children's health inspection program which is more focused on mouth and teeth’s health. Along with the rapid development of technology of internet, the online games makes the gamer or doer especially on students that spend their time in playing online games with no limited time. It is that spark children's eyes health be declining due to the onset of eyestrain complaining and it will affect the quality of human resources in the future. This analysis aims to connect the behavior of students with eyestrain complaining about online games in Padang Bulan area, Medan 2013. The designed of this analysis is cross-sectional. The population in this analysis were all young people by age of 10-18 years in Padang Bulan Area, Medan. Samples are 96 respondents were obtained by accidental sampling. Collecting data through interviews using questionnaires. An analysis of data was done with univariate and bivariate by using chi square test. The results showed that from the 96 respondents, 51 people (53.1%) were often complaints of eyestrain. The symptoms of eyestrain that often be perceived is that the eyes feeling sore and watery were 38 respondents (39.6%). The characteristics of respondents who experienced of eyestrain complaints are men (51%) by age 13-15 years (27.1%) with secondary education (27.1%). From the bivariate data analysis by using chi square test, it was gained a correlation of knowledge (p = 0.016) and the attitude of the respondents (p = 0.030) on the online games that complaints of eyestrain.Based on the results of the analysis, it was suggested that knowledge and attitudes are both to be maintained and further improved, while the poor Juvenile attitude in order to get more attention and the chance to play online games should be reduced in order that the complaints of eyestrain is not often perceived.Keywords: Juvenile Behavior, Online Games , Eyestrain Complaints